THE ACTIVITY AND MECHANISM OF CARDIOPROTECTIVE OF SPIRULINA PLATENSIS G. AND MOMORDICA CHARANTIA L. IN THE PREVENTION OF HEART DAMAGE IN RAT MODELS OF MYOCARDIAL INFARCTION - Kalih Prasesti, Gayuk
Myocardial infarction or what is known to the public as a heart attack, is a disease that causes death or necrosis of the heart muscle due to prolonged ischemia. Spirulina platensis and Momordica charantia are reported to have activity as wound healing and antioxidants. The purposes of this research are to explain the activity and mechanism of cardioprotective action of Spirulina platensis and Momordica charantia extracts and their combination (SPMC). The research started with in vivo evaluation of each sample and the combination given to rats induced with isoproterenol, as a model of heart attack. The study continued with the determination of effective combination dose, toxicity testing, studying the mechanism of action on SIRT1 and the pro-inflammatory cytokine interleukin-1?. Finally, in silico studies and identification of predicted bioactive compounds that have a cardioprotective effect were performed. The characteristics of Spirulina platensis and Momordica charantia crude drugs met the quality requirements based on the specified reference values. Phytochemical screening showed that the water extract of Spirulina platensis contained flavonoids and tannins, while the ethanol extract of Momordica charantia contained flavonoids, tannins and alkaloids. In vivo studies to evaluate cardioprotective activity showed that combination of SPMC extracts was better than each extract. SPMC 50:50 mg/kg bw significantly (P<0.05) inhibited the increase in cardiac biomarker levels. The levels of SGOT (198.27 ± 6.53 mg/dL), CK (185.82 ± 33.98 mg/dL), CK-MB (249.3 ± 17.24 mg/dL) and LDH (444.58 ± 50.95 mg/dL) in rat heart attack model were significantly lower compared with positive controls, the levels of SGOT (232.78 ± 20 mg/dL), CK (393.2 ± 23.1 mg/dL), CK-MB (549.05 ± 56 mg/dL) and LDH (963.21 ± 93 mg/dL). Cell integrity, intact cell nuclei and minimal leukocyte infiltration compared to the positive control group were also shown in the histopathological analysis of the group that received the SPMC combination. Based on cardiac biomarker parameters, infarct area and histopathological analysis, the combination of 50:50 mg/kg bw SPMC extract had the best cardioprotective activity compared to combinations of 25:75 and 75:25 mg/kg bw. In the acute toxicity test, SPMC at a dose of 5 grams/kg bw. did not induce signs of toxicity in terms of behavior and body weight. Macroscopic presentation of the examined organs appeared normal and no deaths were found after 14 days of SPMC administration. The toxicity category based on POM guidelines is classified into category 5 (Unclassified), which is safe. The mechanism of action study was carried out using a combination of Spirulina platensis and Momordica charantia extracts on the SIRT1 protein in vivo and in vitro. Administration of SPMC 50 mg/kg and50 mg/kg bw was able to inhibit a significant increase in levels of the pro-inflammatory cytokine interleukin-1? (639.41 ± 55 pg/mL) compared to the positive control group (1208.25 ± 57 pg/mL). The levels of serum SIRT1 levels in the negative control group, positive control, combination of 50:50 mg/kg bw extract and resveratrol were 0.594 ± 0.03 ng/mL; 0.668 ± 0.02 ng/mL; 0.83 ± 0.04 ng/mL and 0.84 ± 0.05 ng/mL. SPMC significantly increased serum SIRT1 levels compared to the negative control group (P<0.05). Administration of SPMC at concentrations of 1 ppm, 10 ppm and 100 ppm did not reduce the viability of primary cardiomyocyte and the H9C2 cell line. In the molecular study, administration of 100 ppm SPMC also increased SIRT1 expression in the H9C2 cell line. The in silico study showed that the compound phycocyanobilin at a level of 4.18 mM was identified in the Spirulina platensis sample, while in the Momordica charantia sample the compound momordicoside A was detected at 0.54 mM. The compounds phycocyanobilin and momordicilin had the good binding energy to the SIRT1 protein (PDB ID: 4ZZJ) of -10.98 kJ/mol and -11.3 kJ/mol respectively. The comparator resveratrol had the binding energy of (-8.17 kJ/mol). These results indicate that the compounds in Spirulina platensis and Momordica charantia are predicted to also have potential as SIRT1 activators. Taken together, the results of the present study indicate that the combination of Spirulina platensis and Momordica charantia extracts at a dose ratio of 50:50mg/kg provides a better cardioprotective effect compared to each extract alone. The combination also has a good safety profile. SPMC has cardioprotective activity by inhibiting the increase in IL-1?and increase SIRT-1 protein expression in cardiac cells and increasing serum SIRT1.